A Discourse Analysis of Speeches made by Nobel Prize Winners in English Literture - Bùi Thị Hải Vân (2012)
This study is carried out with a view to discover features of English speeches made by Winners of the Nobel Prize in Literature. With the examples of English speeches collected, this thesis focuses on analyzing and comparing the layout features, the ….